Ізоферментний склад персика (Persica vulgaris Mill.) - Kudrenko, I.K.; Kashevarov, G.P.; Moroz, P.А. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The article is dedicated to investigation of isozymes composition of Persica vulgaris Mill. breeding pool. History of creation of peach collection in M.M. Gryshko National Botanical Gardens is given. Potentiality of using isozymes analyze in breeding work was determined. Conclusion is made about the possibility of using peroxidase isozymes as a molecular marker for breeding of peach for winter-tolerance.